Perceived impact of physically active learning portfolio: insights from English language teachers in Türkiye - Demir Yildiz, Canan (Springer, 2025)
The objective of this study is to assess the impact of the Physically Active Learning Portfolio (PALP) on English language teachers' inclination towards incorporating sports-related activities into their teaching practices, as well as their perceptions of these activities. PALP activities were developed with the aim of enhancing English teachers' abilities to integrate various physical movements into course content, fostering an active, healthy, and enjoyable learning environment, and leveraging movement to facilitate rapid and enduring learning outcomes. This study sought to facilitate collaboration between physical education experts and English teachers to integrate movement into language learning. The study group comprised 30 English teachers selected from various public schools across different cities in T & uuml;rkiye, constituting the study's participant cohort. The research design employed in this study was an explanatory sequential mixed-method approach (Creswell et al. in Research design: Qualitative, quantitative, and mixed methods approaches, Thousand Oaks, 2003), where quantitative findings guided the qualitative exploration. Quantitative analysis indicated a statistically significant improvement in only one of the measured dimensions-teachers' personal interest in participating in PALP activities-while no significant changes were observed in other areas. These results suggest that the intervention had a targeted but limited effect within the scope of the short-term implementation. It is important to note that the study employed a single-group pretest-posttest design without a control group, and the small, homogenous sample (N = 30) limits the generalizability of the findings. Nevertheless, qualitative findings provided additional insights into teachers' positive perceptions and their expressed willingness to apply movement-based strategies in their language instruction.
Keywords: Active Learning; Physical Movement; English Language; Teachers; Sports